Mabadi' al-Adab al-Islami 'ind Najib al-Kilani fi Riwayat 'Ibaratal-Hubb al-Malayuwiyyah - Mohd Taufiq, Abd. Talib; Wan Abdul Hayyi, Wan Omar; Mohd Shahrizal, Nasir (2014)
The aim of this research is to investigate the definition of Islamic literature by Najib al-Kilani through the popular Malay novel, “Expressions of Love”. From this research, the Islamic literary features can be examined in terms of its presence in the Malay literary work. In order to achieve this objective, the researchers used both descriptive and analytical methods to define and analyse Islamic literature as presented by Najib al-Kilani in the novel. The findings revealed that Najib al-Kilani’s definition of Islamic literature is global in nature as such features are present in the popular Malay novel.